Two step esterification–transesterification process of wet greasy sewage sludge for biodiesel production. (January 2016) - Urrutia, C.; Sangaletti-Gerhard, N.; Cea, M.; Suazo, A.; Aliberti, A.; Navia, R.
Highlights: A two-step process was tested for using wet greasy sludge in biodiesel production. Acid catalyst showed higher FFA esterification compared to TAG transesterification. Enzymatic catalyst first hydrolyzed TAG in FFA, which were esterified to biodiesel. Alkaline transesterification reached a FAME yield of 65.4% when using acid catalyst. Abstract: Sewage sludge generated in municipal wastewater treatment plants was used as a feedstock for biodiesel production via esterification/transesterification in a two-step process. In the first esterification step, greasy and secondary sludge were tested using acid and enzymatic catalysts. The results indicate that both catalysts performed the esterification of free fatty acids (FFA) simultaneously with the transesterification of triacylglycerols (TAG). Acid catalyst demonstrated better performance in FFA esterification compared to TAG transesterification, while enzymatic catalyst showed the ability to first hydrolyze TAG in FFA, which were esterified to methyl esters. In addition, FAME concentration using greasy sludge were higher (63.9% and 58.7%), compared with those of secondary sludge (11% and 16%), using acid and enzymatic catalysts, respectively. Therefore, only greasy sludge was used in the second step of alkaline transesterification. The alkaline transesterification of the previously esterified greasy sludge reached a maximum FAME concentration of 65.4% when using acid catalyst.